O modelo do votante majoritário em regimes de baixa e alta desordem - Nascimento, Francisco Israel Alves do (2019)
A study of the non-equilibrium phase transition from the majority voter model is presented. A hyperbolic distribution was implemented as the noise of the system in order to create low and high disorder regimes. In this way, we analise the effects of different levels of disorder over systems defined by multiple states, changing the range of interactions. With this in mind, our parameter space is defined by of the number of states S, the number of neighbors Nv and the parameter β that controls the disorder level on the noise distribution. We concentrate the analysis on systems described by S = 2, 3 and 4. Monte Carlo simulations and finite-size scaling theory were used to compute the dependence of the magnetization (The control parameter), the susceptibility and the Binder’s cumulant on the parameter space of the model. We show that for each value of S, the model describes a like order-disorder continuum phase transition where the critical exponents are the same as the ones the correspondent equilibrium models.